STUDI FAUNA TIKUS DAN CECURUT DI DAERAH DITEMUKAN KASUS LEPTOSPIROSIS DI KABUPATEN KLATEN, PROVINSI JAWA TENGAH - Bina Ikawati; Bambang Yunianto (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2011)
Data obtained from Central Java Health Province Agency showed there were six districts of cities with leptospirosis problem. Leptospirosis cases in Klaten District was third sequence after Semarang City and Demak District. Research that had been done in Klaten focused in Jogonalan Sub district. In 2009-2010 leptospirosis cases found in outside Jogonalan. The aims of this research was to identifying of rats and suncus in leptospirosis area at Klaten district. This research was an observasional research using ecology study. Rat trapped and had been done in this research followed by rat identification.Data were analyzed by simple statistic include tabulating, quantifying, multiplication presented in table or graph. Result of this research showed that from three study locations, trap success Kalikotes was showed highest (11,5%), while Wonosari and Gantiwarno was respectively 6,3% and 4,5%. Shanon Wiener Diversity Index was low (<1).Rattus tanezumi was the dominant species.